Liberating and Humane Education Principles in The Perspective of Islamic Education: Analysis of Paulo Freire's Thought - Sudarman Sudarman (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
The education system proposed by Paulo Freire is an educational model that can liberate the verbal and mechanistic human culture. Such a culture, according to Freire, is impossible to lead people to a more authentic and more human life. To achieve this, descriptive educational habits are expected to be shifted towards transformative-dialogue education, so that education is not perceived as a shackling education. Education is expected to produce changes to students, both changes in the quality of thinking, personal quality, social quality, quality of independence and quality of society. That is the paradigm shift of Islamic education, that is changing the paradigm of authoritarian to democratic paradigm, closed to openness, doctrinaire to participatory. Society needs to civilize the tradition of criticism, dialogue, openness, the spirit of pluralism and practical practices that touch the problems of the weak and oppressed by anything politically, economically, socially and culturally.